2015
DOI: 10.1007/jhep07(2015)173
|View full text |Cite
|
Sign up to set email alerts
|

Critical point in the QCD phase diagram for extremely strong background magnetic fields

Abstract: Lattice simulations have demonstrated that a background (electro)magnetic field reduces the chiral/deconfinement transition temperature of quantum chromodynamics for eB < 1 GeV 2 . On the level of observables, this reduction manifests itself in an enhancement of the Polyakov loop and in a suppression of the light quark condensates (inverse magnetic catalysis) in the transition region. In this paper, we report on lattice simulations of 1 + 1 + 1-flavor QCD at an unprecedentedly high value of the magnetic field … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 92 publications
10
85
2
Order By: Relevance
“…Under an increase of the magnetic field, the CEP eventually moves toward μ B ¼ 0, and the deconfinement and chiral phase transitions should become of first order as predicted by lattice calculations [49].…”
Section: The Influence Of the Magnetic Field On The Isentropic Tramentioning
confidence: 78%
“…Under an increase of the magnetic field, the CEP eventually moves toward μ B ¼ 0, and the deconfinement and chiral phase transitions should become of first order as predicted by lattice calculations [49].…”
Section: The Influence Of the Magnetic Field On The Isentropic Tramentioning
confidence: 78%
“…Nevertheless, external magnetic field effects are best included through the Schwinger Proper-Time representation of the fermion propagator. This observation has been exploited to address the problem of magnetic catalysis [12] and inverse magnetic catalysis observed in lattice simulations [13,14] and confirmed by several approaches [7,8,15]. Under this environment, the effective coupling of the model can reach very large values, and therefore, exploring the validity of these regularization schemes in this super-strong coupling regime is a natural question to address.…”
Section: Introductionmentioning
confidence: 76%
“…6: Plots of the critical temperature against eB, TC0 = 160MeV. We show the best fit lattice data taken from [8] and the holographic models best fit to that data (κ = 0.05, a = 0, b = 0.037). We also show the holographic models prediction for another value of b = 0.33 -the model depends on the quantity bB 2 so the eB axis is simply rescaled by this change.…”
Section: Magnetic Fieldmentioning
confidence: 95%
“…Recent lattice studies of QCD with light quarks and an applied magnetic field [6][7][8] have revealed some surprisingly complex behaviour. At zero temperature the magnetic field enhances the chiral condensate σ ≡ qq -"magnetic catalysis" -as has generally been predicted [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%